1988
DOI: 10.1002/dc.2840040207
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical presentation of alpha‐fetoprotein‐producing gastric cancer in ascitic fluid: A case study

Abstract: A case of primary gastric cancer without hepatic metastasis showing extremely high alpha-fetoprotein (AFP) levels is reported. This case illustrates the application of the immuno-peroxidase technique to ascitic fluid cytology. Papanicolaou-stained smears of the ascites permitted the diagnosis of a metastatic carcinoma. A positive reaction to AFP was demonstrated in the tumor cells in the ascitic fluid cellular samples as well as in the paraffin-embedded tissue section of the primary gastric carcinoma. Rising A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…2 As a diagnostic basis, serum AFP levels of most AFPGC were only slightly higher than normal, but in some cases, the serum AFP levels were even beyond the detection limit. [3][4][5] In some AFPGCs, it was observed that certain lesions mimicked HCC-like morphology under a light microscope. The lesions were composed of large, polygonal cells with abundant eosinophilic cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…2 As a diagnostic basis, serum AFP levels of most AFPGC were only slightly higher than normal, but in some cases, the serum AFP levels were even beyond the detection limit. [3][4][5] In some AFPGCs, it was observed that certain lesions mimicked HCC-like morphology under a light microscope. The lesions were composed of large, polygonal cells with abundant eosinophilic cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…As a diagnostic rule, serum AFP levels of most AFPGC were only slightly higher than normal, but in some cases, they were as high as several thousand ng/mL or more, even beyond the detection limit [15][16][17]. Some researchers observed that certain lesions mimicked HCC-like morphology under the light microscope, especially in these AFPGCs with high serum level of AFP.…”
Section: Introductionmentioning
confidence: 99%
“…TRACT [36][37][38][39][40][41][42][43][44][45] Gastrointestinal carcinomas develop malignant effusions in 20-30% of cases. In men they are the most common cause and in women the second most common cause of malignant peritoneal effusions.…”
Section: Carcinomas Of the Gastrointestinalmentioning
confidence: 99%